Effect of bimodularity and thermomechanical stresses from composite curing on mixed-mode fracture behavior of functionally graded skin-stiffener runout - Shah S.; Panda S.K. (My University, 2025)
The present work illustrates the influence of bimodulus polarity and curing stress on interface delamination in skin stiffener runout. In contrast to unimodular assumptions, the bimodulus skin stiffener’s fracture behavior is much more unsymmetrical depending on the sequential thermo-mechanical loading. The numerical study has been done to demonstrate debonding and delamination with the help of the Virtual Crack Closure Technique on compliant runout configuration under varying bimodular ratios. The modified design of the runout has been displayed, and different design configurations have been compared to determine the merits of the design of skin-stiffener runout: a baseline configuration, a tip-tapered configuration, and notch-tapered configuration with the functionally graded bimodular property. A three-dimensional finite element-based analysis has been performed on these configurations to evaluate the strength and damage tolerance. Also, the Strain Energy Release Rate has been assessed for non-identical loading and boundary conditions. It has been found that bimodularity significantly reduces failure growth. This analysis aims to decelerate the interfacial fracture extension rate by introducing functionally graded bimodularity in the structure. © 2021 Taylor & Francis Group, LLC.